Quantifying cobalt in doping control urine samples--a pilot study - Krug, Oliver; Kutscher, Daniel; Piper, Thomas; Geyer, Hans; Schänzer, Wilhelm; Thevis, Mario (Drug testing and analysis, 2014)
Since first reports on the impact of metals such as manganese and cobalt on erythropoiesis were published in the late 1920s, cobaltous chloride became a viable though not widespread means for the treatment of anaemic conditions. Today, its use is de facto eliminated from clinical practice; however, its (mis)use in human as well as animal sport as an erythropoiesis-stimulating agent has been discussed frequently. In order to assess possible analytical options and to provide relevant information on the prevalence of cobalt use/misuse among athletes, urinary cobalt concentrations were determined by inductively coupled plasma-mass spectrometry (ICP-MS) from four groups of subjects. The cohorts consisted of (1) a reference population with specimens of 100 non-elite athletes (not being part of the doping control system), (2) a total of 96 doping control samples from endurance sport athletes, (3) elimination study urine samples collected from six individuals having ingested cobaltous chloride (500 µg/day) through dietary supplements, and (4) samples from people supplementing vitamin B12 (cobalamin) at 500 µg/day, accounting for approximately 22 µg of cobalt. The obtained results demonstrated that urinary cobalt concentrations of the reference population as well as the group of elite athletes were within normal ranges (0.1-2.2 ng/mL). A modest but significant difference between these two groups was observed (Wilcoxon rank sum test, p < 0.01) with the athletes' samples presenting slightly higher urinary cobalt levels. The elimination study urine specimens yielded cobalt concentrations between 40 and 318 ng/mL during the first 6 h post-administration, and levels remained elevated (>22 ng/mL) up to 33 h. Oral supplementation of 500 µg of cobalamin did not result in urinary cobalt concentrations > 2 ng/mL. Based on these pilot study data it is concluded that measuring the urinary concentration of cobalt can provide information indicating the use of cobaltous chloride by athletes. Additional studies are however required to elucidate further factors potentially influencing urinary cobalt levels.